Hydrodynamics Regulate Longitudinal Plankton Community Structure in an Alpine Cascade Reservoir System - Liu, Yang; Li, Chengyan; Jian, Shenglong; Miao, Shiyu; Li, Kemao; Guan, Hongtao; Mao, Yaqi; Wang, Zhongyi; Li, Changzhong (Frontiers in Microbiology, 2021)
Previous studies report significant changes on biotic communities caused by cascade reservoir construction. However, factors regulating the spatial-temporal plankton patterns in cascade reservoir systems have not been fully explored. The current study explored effects of environmental factors on the longitudinal plankton patterns, through a 5-year-long study on the environmental factors and communities of phytoplankton and zooplankton in an alpine cascade reservoir system located upstream of Yellow River region. The findings showed that phytoplankton and zooplankton species numbers in the studied cascade reservoir system were mainly regulated by the hydrological regime, whereas nutrient conditions did not significantly affect number of species. Abundance and biovolume of phytoplankton in cascade reservoirs were modulated by the hydrological regime and nutrient conditions. The drainage rate, N:P ratio and sediment content in cascade reservoirs were negatively correlated with abundance and biovolume of phytoplankton. Abundance and biovolume of zooplankton were no significantly correlated with the hydrological regime but showed a strong positive correlation with nutrient conditions in cascade reservoirs. Shannon-Wiener index (H’) and the Pielou index (J) of phytoplankton were mainly regulated by the hydrological regime factors, such as drainage rate and sediment content in cascade reservoirs. However, temperature and nutrient conditions were the main factors that regulated the Shannon-Wiener index (H’) and the Pielou index (J) of zooplankton. Species number, abundance, and biovolume of phytoplankton showed a significant positive correlation with those of zooplankton. These findings provide an understanding of factors that modulate longitudinal plankton community patterns in cascade reservoir systems and provide a basis for further studies.